Respuesta :

Step-by-step explanation:

For this problem, we can simply plug in the coordinate point into the given formula.

(-8, 6) = (-8 + 5, 6 - 4)

(-8, 6) = (-3, 2)

So, A' is at point (-3, 2)

Now, we have to find the distance from A to A'. We can use the distance formula.

[tex]d=\sqrt{(x2-x1)^2+(y2-y1)^2}[/tex]

[tex]d=\sqrt{(-3-(-8))^2+(2-6)^2}[/tex]

[tex]d=\sqrt{(5)^2+(-4)^2}[/tex]

[tex]d=\sqrt{25+16}[/tex]

[tex]d=\sqrt{41}[/tex]

So, the distance between A and A' is about 6.4 units.

ACCESS MORE